2020
DOI: 10.1371/journal.pone.0238134
|View full text |Cite
|
Sign up to set email alerts
|

3D imaging of undissected optically cleared Anopheles stephensi mosquitoes and midguts infected with Plasmodium parasites

Abstract: Malaria is a life-threatening disease, caused by Apicomplexan parasites of the Plasmodium genus. The Anopheles mosquito is necessary for the sexual replication of these parasites and for their transmission to vertebrate hosts, including humans. Imaging of the parasite within the insect vector has been attempted using multiple microscopy methods, most of which are hampered by the presence of the light scattering opaque cuticle of the mosquito. So far, most imaging o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Individuals who have greater genetic liability for using cannabis may use cannabis more frequently, which has been associated with cortical alterations. 40,41 For example, work by Chye et al 12,41 indicated that adolescents who used cannabis showed reduced thickness in the bilateral insula, a brain region that has been closely linked to addictive behaviors, including craving and drug-seeking, interoceptive processing, response to reward, and impulsive decision making. 42,43 Other work has shown that individuals who initiate cannabis use had a smaller insula surface area in the right hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who have greater genetic liability for using cannabis may use cannabis more frequently, which has been associated with cortical alterations. 40,41 For example, work by Chye et al 12,41 indicated that adolescents who used cannabis showed reduced thickness in the bilateral insula, a brain region that has been closely linked to addictive behaviors, including craving and drug-seeking, interoceptive processing, response to reward, and impulsive decision making. 42,43 Other work has shown that individuals who initiate cannabis use had a smaller insula surface area in the right hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…This approach applied to chemically-cleared Drosophila adult male individuals allowed to just use the AF of the sample to image both surface (e.g., hexagons of the lens facets, bristles on inter-ommatidial, maxillary palp and distal labellum) and internal (e.g., elements of the compound eye, the optic lobe, cardia) structures, to be made then observable with a highly sharp resolution in a 3D virtual reconstruction [165]. The 3D imaging analysis has been thus used as a technique additional to conventional optical or scanning electron microscopy, and its ability to provide variable views of the target organism has stimulated both new investigations to improve sample preparations, or applications to improve the detection of parasites (e.g., Plasmodium in infected A. stephensi) [36,166,167]. Sample clearing with KOH has been thus recommended as the preferred preparation procedure to obtain specimens suitable to be preserved for long time and thus for reexaminations by confocal microscopy, favoring sample exchange among scientists and comparative and taxonomic studies.…”
Section: High Resolution Morphologymentioning
confidence: 99%
“…In this context, efforts have been devoted to circumvent the problem. Different optical clearing methods and microscope imaging procedures have been compared, in order to improve the localization of Plasmodium parasites in the midgut of Anopheles vectors [ 36 ]. On the other hand, Koga and colleagues have developed a protocol based on the use of hydrogen peroxide able to strongly reduce AF in insect tissues and allow a reliable FISH detection of endosymbionts of aphids, lice and bat flies [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations